INTERPRETASI PENERAPAN AKUNTANSI ASET TETAP BERDASARKAN PSAK 16 PADA BPJS KETENAGAKERJAAN TAHUN 2023 - Islamiyah, Anisa; Nufaisa, Nufaisa (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, 2024)
Fixed assets are one of the important elements in the financial statements because they support the organization's operations. PSAK 16 regulates the recognition, measurement, depreciation, and reporting of fixed assets to make the financial statements transparent and reliable. BPJS Ketenagakerjaan as a public legal entity manages fixed assets such as investment property, buildings, and office equipment that play a strategic role in providing services to the community. This study aims to evaluate the application of fixed asset accounting in BPJS Ketenagakerjaan in 2023 based on PSAK 16. This research uses a descriptive qualitative approach with a comparative method. The research population is the financial statements of BPJS Ketenagakerjaan in 2023 with samples in the form of data related to fixed assets. The results showed that the grouping of fixed assets and depreciation using the straight-line method were in accordance with PSAK 16. However, in the recognition of fixed asset acquisition costs, BPJS Ketenagakerjaan has not fully capitalized related costs such as transportation and installation which can affect the accuracy of financial statements. Overall, the implementation of PSAK 16 in BPJS Ketenagakerjaan is good, but further evaluation is needed to improve accountability and transparency.